Halichoerus grypus - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Halichoerus grypus (Fabricius 1791) [Phoca] grypus Fabricius 1791, Skr. Nat. Selsk. Copenhagen, 1 (2): 167. Type Locality: Listed by Scheffer (1958) as " Greenland ". Vernacular Names: Gray Seal. Subspecies:: Subspecies Halichoerus grypus subsp. grypus Fabricius 1791 Subspecies Halichoerus grypus subsp. macrorhynchus Hornschuch and Schilling 1851 Distribution: Temperate and subarctic waters around Canada (Newfoundland area), Denmark, Estonia, Finland, France, Germany, Great Britain, Greenland, Iceland, Ireland, Latvia, Lithuania, Netherlands, Norway, Portugal (vagrant), Russia (Kola Peninsula), Sweden, USA (Maine, New Hampshire, Massachusetts, New Jersey - vagrant). Conservation: IUCN – Lower Risk (lc), except for Northeast Atlantic subpopulation, which is Endangered. Discussion: Synonyms allocated according to Ellerman and Morrison-Scott (1951). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 596, DOI: 10.5281/zenodo.7316519